Clinical Evaluation Of Post High Tibial Osteotomy Patients In Regional General Hospitals Dr. Soetomo Surabaya, Husada Utama Hospital Surabaya, Al-Irsyad Hospital Surabaya In 2010 - 2015 - Limbong, Suyenci; Utomo, Dwikora Novembri (Qanun Medika - Medical Journal Faculty of Medicine Muhammadiyah Surabaya, 2019)
ABSTRACT Osteoarthritis (OA) of the knee is a disruption in the knee joint which is characterized by pathological changes in the structure in the knee joint that occur progressively. High Tibial Osteotomy (HTO) is a therapeutic option for treating isolated medial compartment OA in varus genu and one of the routine surgical procedures performed in the orthopedic field. As the number of OA cases increases, the number of high tibial osteotomy (HTO) procedures also increases, so clinical evaluation is needed to see whether HTO can meet patient expectations. This study was a retrospective descriptive study with a sample of patients who had undergone the 2010 to 2015 open wedge high tibial osteotomy (OWHTO) procedure. The evaluation used the Knee Society Score, Knee Injury and Osteoarthritis Outcome Score, and Modified Hospital instruments for Special Surgery Knee Scoring. The data obtained are then grouped and analyzed to calculate the average of each instrument. The results showed a sample of 6 knees consisting of 2 male samples (33.3%) and 4 female samples (66.7%). All samples are over 35 years old. The evaluation results using KOOS scores obtained the mean value of the pain component was 77.7; complaint component = 70.3; daily activity component = 76.2; sports and recreation components = 47.9; and components of quality of life = 74.1. On the SSC score, the average knee score was 70.8 and the average functional score was 61.6. Whereas the HSS score obtained by the average functional score is 81.5. This study produced each score with a good average value. This shows that the choice of the High Tibial Osteotomy operating technique provides satisfactory operating results. So that the High Tibial Osteotomy surgery technique can be an option in the case of Osteoarthritis. With the many choices of types of surgery in patients with Osteoarthritis, the High Tibial Osteotomy can be a good choice for patient satisfaction. Keywords: Osteoarthritis, High Tibial Osteotomy, Knee Society Score, Knee Injury and Osteoarthritis Outcome Score, Modified Hospital for Special Surgery Knee Scoring Correspondence to: liliosanci@gmail.com ABSTRAK Osteoartritis (OA) lutut adalah gangguan pada sendi lutut yang ditandai oleh perubahan patologis pada struktur di dalam sendi lutut yang terjadi secara progresif. High Tibial Osteotomy (HTO) merupakan pilihan terapi untuk penanganan isolated medial compartement OA pada genu varus dan salah satu prosedur operasi yang rutin dilakukan di bidang orthopedi. Dengan meningkatnya jumlah kasus OA meningkat pula jumlah prosedur high tibial osteotomy (HTO), sehingga perlu dilakukan evaluasi klinis untuk melihat apakah HTO dapat memenuhi harapan pasien. Penelitian ini merupakan penelitian deskriptif retrospektif dengan sampel pasien yang telah menjalani prosedur open wedge high tibial osteotomy (OWHTO) 2010 sampai 2015. Evaluasi menggunakan instrument Knee Society Score, Knee Injury and Ostoarthritis Outcome Score, dan Modified Hospital for Special Surgery Knee Scoring. Data yang didapat selanjutnya dikelompokkan dan dianalisa utk menghitung rata-rata dari masing-masing instrumen. Hasil penelitian didapatkan sampel sejumlah 6 lutut yang terdiri dari 2 sampel laki-laki (33,3%) dan 4 sampel perempuan (66,7%). Semua sampel berusia di atas 35 tahun. Hasil evaluasi menggunakan skor KOOS didapatkan nilai rerata komponen nyeri adalah 77,7; komponen keluhan = 70,3; komponen aktivitas harian = 76,2; komponen olahraga dan rekreasi = 47,9; dan komponen kualitas hidup = 74,1. Pada skor KSS didapatkan rerata knee score adalah 70,8 dan rerata functional score adala 61,6. Sedangkan pada skor HSS didapatkan rerata functional score adalah 81.5. Penelitian ini menghasilkan masing-masing skor dengan nilai rata-rata yang bagus. Hal ini menunjukkan bahwa pilihan teknik operasi High Tibial Osteotomy memberikan hasil operasi yang memuaskan. Sehingga teknik operasi High Tibial Osteotomy dapat menjadi salah satu pilihan pada kasus Osteoarthritis. Dengan banyaknya pilihan macam operasi pada penderita Osteoarthritis maka High Tibial Osteotomy dapat menjadi satu pilihan yang baik untuk kepuasan pasien. Kata kunci: Osteoartritis, High Tibial Osteotomy, Knee Society Score, Knee Injury and Ostoarthritis Outcome Score, Modified Hospital for Special Surgery Knee Scoring Korespondensi: liliosanci@gmail.com